The Efficacy of Generic Daclatasvir-Sofosbuvir as Pan-Genotypic Regiment for Hepatitis C Virus (HCV) Infected Patients in Bandung Indonesia - Muhammad Begawan Bestari; Eka Surya Nugraha; Siti Aminah Abdurachman (The Indonesian Society for Digestive Endoscopy, 2020)
Background: Direct-acting antivirals (DAAs) have altered the prognosis of hepatitis C virus (HCV) disease but its access is limited by socioeconomic factors. Generic DAAs with lower prices were available in Indonesia in 2016. The aim of this study was to determine the efficacy of generic daclatasvir-sofosbuvir.Method: We performed an observational study from January to December 2016 in a tertiary care center in Bandung, Indonesia. Data were obtained from medical registry. All study subjects received oral daclatasvir (60 mg, once daily) and sofosbuvir (400 mg, once daily) for 12 weeks for noncirrhotic chronic HCV patients and 24 weeks for cirrhotic chronic HCV patients. The main endpoint criterion was sustained virologic response at post-treatment week 12 (SVR12).Results: We enrolled 32 subjects (20 noncirrhotic, 12 cirrhotic). All noncirrhotic subjects (eighteen were previously untreated patients) and cirrhotic subjects (all were previously untreated patients) achieved SVR12 of 100%. These high rates of SVR12 were observed in all patients with HCV infection regardless of the genotype. ALT normalization was achieved in all patients 12 weeks after therapy. The most common adverse events were fatigue and nausea.Conclusion: Once-daily oral generic daclatasvir-sofosbuvir showed good efficacy and safety. Furthermore, it yielded a high rate of SVR among patients infected with HCV of all genotypes.